Queer tidalectics : linguistic and sexual fluidity in contemporary Black diasporic literature - Amideo, Emilio (Critical insurgencies., 2021)
"Queer Tidalectics investigates how Anglophone writers James Baldwin, Jackie Kay, Thomas Glave, and Shani Mootoo employ the trope of fluidity to articulate a Black queer diasporic aesthetics"--